2019
DOI: 10.1002/cctc.201900220
|View full text |Cite
|
Sign up to set email alerts
|

N‐Heterocyclic Carbene Non‐Innocence in the Catalytic Hydrophosphination of Alkynes

Abstract: Studies on alkyne hydrophosphination employing nickel‐NHC catalysts (NHC=N‐heterocyclic carbene) revealed that the free N‐alkyl substituted NHCs themselves were catalytically active. DFT calculations showed the mechanism involves the NHC acting as a Brønsted base to form an imidazolium phosphide species which then undergoes rate‐limiting nucleophilic attack at the terminal alkyne carbon. This mechanism explains the preference seen experimentally for reactions with aryl substituted phosphines and alkynes, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Having shown the influence of the sterics on the reductive elimination process, we wondered if we could show its implications in catalysis. Recently, some of us reported that N -alkyl substituted N -heterocyclic carbenes NHCs can promote the anti-Markovninov hydrophosphination of terminal alkynes, whereas Et CAAC fails to catalyze this reaction. Capitalizing on our findings, we found that the bulkier Menth CAAC 2 (10 mol %) allows for the anti-Markovninov hydrophosphination of phenyl acetylene with diphenylphosphine in full conversion after 16 h at 60 °C (Scheme ).…”
mentioning
confidence: 99%
“…Having shown the influence of the sterics on the reductive elimination process, we wondered if we could show its implications in catalysis. Recently, some of us reported that N -alkyl substituted N -heterocyclic carbenes NHCs can promote the anti-Markovninov hydrophosphination of terminal alkynes, whereas Et CAAC fails to catalyze this reaction. Capitalizing on our findings, we found that the bulkier Menth CAAC 2 (10 mol %) allows for the anti-Markovninov hydrophosphination of phenyl acetylene with diphenylphosphine in full conversion after 16 h at 60 °C (Scheme ).…”
mentioning
confidence: 99%
“…Finally, ItBu acts itself as a base in the deprotonation of diphenylacetonitrile with no contribution from the metallic component. The catalytic role of NHC Brønsted basicity in hydrophosphination has recently been elucidated 54 and further progress in non-metallic catalysis constitutes an interesting future endeavour for us.…”
Section: Discussionmentioning
confidence: 99%
“…This regiochemistry/NMR chemical shift has been reported by several others. 10 21 Work from Bookham, 22 which uses diphenylacetylene as a substrate, 23 reports the Z -product (( Z )-(1,2-diphenylvinyl)diphenylphosphine) at –7.8 ppm and the E -product (( E )-(1,2-diphenylvinyl)diphenylphosphine) at +8.7 ppm. Bookham’s work is cited by Westerhausen as having comparable data to ( E )-diphenyl(1-phenylprop-1-en-2-yl)phosphane, for which a crystal structure is reported.…”
Section: Table 1 Variation Of the Phosphorus Reagent ...mentioning
confidence: 99%